Normese en el código de la democracia la independencia autónoma de los partidos y movimientos políticos en sus decisiones internas por parte del consejo nacional electoral. - Jiménez Pérez, Ulvio César (2013)
When we talk about crisis of political parties, we talk about the gap instauraen policy space as a result of organic decay of structures of power, specialized deregulation votes, which is a dysfunctional relationship between the voter and the institutional space. The phenomenon discredits, all of a sudden, political parties, perceived as machines to generate votes and not as spaces for discharge promises made during the campaign. As a side effect of this dysfunctional relationship, social movements and the citizens have been pressured to participate in the elections in an autonomous manner with respect to the traditional parties, and will generate if their own structures, the features that surround to the time of the foundation are the elements that make up the subdomain that here is collected as the partisan source.As immediately will be highlighted, emphasized the existence of the presence of a certain type of motivation linked to electoral factors, to other strictly extrapartidistas, as would be the so-called indirect structure factors, and for a support organization as substantive elements involved in the process of starting up a political party. A large part of the constitutional reforms developed by the political elite in Ecuador, were inspired by the principle that the participation of citizens in public decision-making would be the "lifeblood" of a democratic regime; in the light of the effects produced in these two decades of study, it was concluded that the proliferation of policy options obtained precisely the opposite result, lock in the political decision-making. As discussed earlier, the tendency to promote the electoral participation is not a sufficient ingredient to consolidate democracy in Ecuador; without a set of party institutions developed, the pure electoral participation resulted in a fragmentation of the party system, with indiscipline electoral favor and disconnection.